Low-dose Flecainide vs Propafenone for Supraventricular Ectopy Suppression in the Elderly - Skakun, Oleksii Zenoviiovych (Eastern Journal of Medical Sciences, 2024)
Frequent premature atrial contractions (PACs) and focal atrial tachycardias (FAT) are seen in one third of patients after ablation for atrial fibrillation. Sometimes first line therapy (beta blockers, verapamil, and diltiazem) is insufficient for proper control of supraventricular ectopy or there are some contraindications to their use. In these cases, antiarrhythmic agents of the IC class (flecainide and propafenone ) are administered. Despite the differences in their pharmacodynamic and pharmacokinetic properties, there is no direct comparison between these two agents regarding their efficacy in suppressing supraventricular ectopy. We report a case of switching from low dose propafenone to low dose flecainide in elderly with frequent PACs and episodes of FAT. An 81 year old man had a high number of symptomatic PACs and episodes of FAT in the settings of propafenone at the dose of 150 mg twice a day after cryoablation for atrial fibrillation. Propafenone was switched to flecainide at a dose of 50 mg twice daily and ambulatory ECG monitoring was repeated. The total number of PACs, FATs and premature ventricular contractions (PVCs) decreased significantly. PAC burden decreased from 18.4% to 7.9%. However, the number of blocked PACs increased from 189 to 2518 per day. Palpitations became less frequent. Thus, low dose flecainide is associated with a decrease in the number of PACs, episodes of FAT and PVCs compared with low dose propafenone, but the number of blocked PACs is higher in the setting of flecainide use.